Multi-targeted pharmacological actions and nanodelivery strategies of Garcinia cambogia: from molecular mechanisms to disease treatment - Zhang, Hang; Cao, Yurou; Chen, Xubin; Chen, Jingxin (Frontiers in Chemistry, 2025)
Garcinia cambogia (Gambogic Acid, GA) is a natural xanthone compound extracted from the resin of GA fruit, renowned for its diverse biological activities and substantial therapeutic potential. GA, a principal bioactive component of Garcinia cambogia, possesses a distinctive cage-like molecular architecture centered on an α,β-unsaturated ketone moiety. This structure is not merely a chemical signature but the fundamental source of GA’s broad and integrated pharmacodynamic profile. While the multi-target nature of natural products like flavonoids has been widely documented, GA’s unique polycyclic caged structure confers a different mechanism of action and a broader spectrum of activity, particularly in epigenetic reprogramming and the activation of multi-modal cell death networks. This review moves beyond a mere compilation of GA’s effects to provide a systematic and critical analysis of its pharmacological landscape. We deconstruct its mechanisms along three integrated dimensions: (i) a molecular-level characterization of GA-regulated signaling pathways, emphasizing its multi-target synergy; (ii) an empirical evaluation of its therapeutic efficacy across cancer and inflammatory diseases, critically appraising both promises and limitations of current evidence; and (iii) an evidence-based discussion on overcoming translational barriers, with a focal point on how innovative nanodelivery strategies are pivotal in resolving GA’s pharmacokinetic challenges. By directly comparing GA with other natural products (e.g., flavonoids) in terms of structure-activity relationships and translational potential, we highlight its unique position in the natural product pharmacopeia. We conclude that the future of GA research lies in the integration of multi-omics approaches with precision drug delivery systems, a synergistic strategy that will effectively bridge the gap between its robust mechanistic underpinnings and successful clinical application.